The AfCFTA impact on agricultural and food trade: a value added perspective - Fusacchia, Ilaria; Balié, Jean; Salvatici, Luca (Oxford University Press, 2022)
The African Continental Free Trade Area agreement will create the largest single market in the world in terms of the number of countries and people. We analyse the effects of regional trade liberalisation on production fragmentation and networks using a global computable general equilibrium model adapted to take into account the value-added structure of international trade. This permits the analysis of the impact of trade policies in the presence of global upstream and downstream linkages through a counterfactual analysis. The analysis goes beyond previous studies by focusing on member countries’ agricultural and food integration in regional and global value chains through backward and forward linkages. Our simulation results suggest that the agreement could have a significant impact on trade patterns in terms of value-added structure and extra- or intra-regional destinations. The reduction in trade costs within the region has a higher incidence on agriculture and food backward intra-regional integration than on forward participation, but this pattern varies substantially across countries. We find that the continental agreement translates in more widely spread benefits across sectors if we consider the income generated within each sector (value added) rather than simply accounting for gross exports.